2013
DOI: 10.1128/mcb.01181-13
|View full text |Cite
|
Sign up to set email alerts
|

The MLL3/MLL4 Branches of the COMPASS Family Function as Major Histone H3K4 Monomethylases at Enhancers

Abstract: Histone H3 lysine 4 (H3K4) can be mono-, di-, and trimethylated by members of the COMPASS (complex of proteins associated with Set1) family from Saccharomyces cerevisiae to humans, and these modifications can be found at distinct regions of the genome. Monomethylation of histone H3K4 (H3K4me1) is relatively more enriched at metazoan enhancer regions compared to trimethylated histone H3K4 (H3K4me3), which is enriched at transcription start sites in all eukaryotes. Our recent studies of Drosophila melanogaster d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
355
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 354 publications
(392 citation statements)
references
References 41 publications
25
355
3
1
Order By: Relevance
“…These observations are consistent with recent studies showing that COMPASS-like MLL3/ MLL4 complexes predominantly monomethylate H3K4 at enhancer regions and specific promoter regions (Herz et al 2012;Hu et al 2013;Morgan and Shilatifard 2013;Cheng et al 2014). Interestingly, upon incubation of the MLL3 SET domain with the Ash2L/RbBP5 complex reconstituted with RbBP5 phos , peaks corresponding to H3K4me1 and H3K4me2 were observed.…”
Section: Rbbp5 Phosphorylation Controls Histone H3k4 Methylation By Ksupporting
confidence: 92%
See 1 more Smart Citation
“…These observations are consistent with recent studies showing that COMPASS-like MLL3/ MLL4 complexes predominantly monomethylate H3K4 at enhancer regions and specific promoter regions (Herz et al 2012;Hu et al 2013;Morgan and Shilatifard 2013;Cheng et al 2014). Interestingly, upon incubation of the MLL3 SET domain with the Ash2L/RbBP5 complex reconstituted with RbBP5 phos , peaks corresponding to H3K4me1 and H3K4me2 were observed.…”
Section: Rbbp5 Phosphorylation Controls Histone H3k4 Methylation By Ksupporting
confidence: 92%
“…MLL1/MLL2 di/trimethylate H3K4 (H3K4me2/3) and regulate Hox gene expression during embryonic development (Yu et al 1995;Dou et al 2006). MLL3/MLL4 regulate adipogenesis ) and primarily monomethylate H3K4 (H3K4me1) at both enhancer (Herz et al 2012;Hu et al 2013) and promoter (Cheng et al 2014) regions, while SET1A/B are the primary H3K4 trimethyltransferases (Wu et al 2008). However, despite divergence in catalytic activity and functional roles, enzymes of the KMT2/COMPASS family must assemble into multisubunit complexes to carry out their biological functions.…”
mentioning
confidence: 99%
“…Our finding is consistent with earlier studies demonstrating that in contrast to Set1a and Set1b, the major H3K4 trimethylases in mammalian cells (30), MLL1 and MLL4, the HMTs known to associate with menin, are responsible for H3K4 trimethylation of only a subset of loci (31). Our observations are also in line with studies showing that MLL1 loss decreased H3K4me3 levels in less than 5% of genes in mouse embryonic fibroblasts (MEFs) and that MLL4 knockdown had no impact on overall H3K4me3 levels in mouse embryonic stem cells (31,32). We previously reported that inactivation of Rbp2 could partially rescue the tumor phenotype in Men1-deficient mice (24).…”
Section: Inactivation Of Men1 Does Not Alter Global H3k4me3 Levels Insupporting
confidence: 91%
“…Nevertheless, our group and others have observed both global and local changes in H3K4me3 at promoters of genes with cancer-promoting activity, in cancer cells (14,25,26,53,54). Methylation of H3K4 is primarily catalyzed by TrxG members, with the modification of H3K4me3 chiefly catalyzed by hSETD1A (26,27,(55)(56)(57)(58). Here, we showed increase in both global H3K4me3 and hSETD1A protein levels in cultured breast cancer cell lines (Fig.…”
Section: Discussionmentioning
confidence: 48%